Extraction and Characterization of Peppermint (Mentha piperita) Essential Oil and its Assessment as Antioxidant and Antibacterial - Siddeeg, Azhari; A. Salih, Zakaria; Mukhtar, Rabab M. E.; O. Ali, Ali (Gezira Journal of Engineering and Applied Sciences, 2018)
ABSTRACT       The aim of this study is to extract and characterize peppermint essential oil and assess it as antioxidant and antibacterial activity. The extraction processes, chemical composition, total phenolic contents (TPC), total flavonoid contents (TFC), antioxidant and antibacterial activity were studied. The oil was extracted by three methods: steam distillation, solvent and soxhelet.  The results indicated that the highest oil extraction was obtained by soxhelet method 1.5±0.12 and 1.2±0.12 ml/100 gm and the lowest result recorded by steam distillation 1.1±0.09 and 0.9±0.14 ml/100gm from fresh and dry samples, respectively. The chemical composition of fresh and dry sample were determined by using gas chromatography and the results showed that there were 26 components of volatile compounds were identified in the essential oil isolated from peppermint. The antibacterial potential of mint essential oils was evaluated by Muller Hinton agar well diffusion method against selected bacteria. The essential oils showed higher activity against Staphylococcus aureus and Salmonella 19±1.41 and 16.5±2.12 mm, respectively, for fresh sample and showed lower activity against Escherichia coli and Klebsilla pneumonia 8.5±0.70 mm and nil, respectively, for dry sample. The TPC of fresh and dry samples were 14.00±0.12 and 8.80±0.09 mg /kg, respectively. TFC of the mint essential oil was determined in comparison with rutin were 8.1±0.09 and 5.0±0.07mg/kg, for fresh and dry sample, respectively. The results showed decrease in peroxide value at 30, 60, 90, 120 and 150 min compared with blank sample without essential oil for wet and dry mint. DPPH inhibition percentages were recorded and inhibition concentrations at 50% activity (IC 50 ) were 0.651±0.09, 0.683±0.6 and 0.161±0.07 mg/mL for wet, dry samples and standard respectively. It can be recommended that further study on sensory analysis of food products containing mint essential oil to evaluate its acceptability and shelf life. .